2020
DOI: 10.3390/molecules25153547
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anthocyanidin Profile on Antileishmanial Activity of Arrabidaea chica Morphotypes

Abstract: Arrabidaea chica Verlot (crajiru) is a plant used in folk medicine as an astringent, anti-inflammatory, wound healing and to treat fungal and viral diseases such as measles chickenpox and herpes. Arrabidaea chica has several morphotypes recognized but little is known about its chemical variability. In the present study the anthocyanidin profile of A. chica morphotypes collected in two seasons (summer and winter) have been examined and their activity against Leishmania infection compared. High-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…299.0924 for C 17 H 15 O 5 ) in combination with its NMR data as previously described [ 12 ]. Carajurin purity was previously determined by HPLC-DAD-UV as 98%, as well as by data from ESI-MS experiments and by NMR 1 H and 13 C data [ 11 ]. The compound was initially described by Chapman et al [ 13 ] and characterized by Zorn et al [ 14 ] and Devia et al [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…299.0924 for C 17 H 15 O 5 ) in combination with its NMR data as previously described [ 12 ]. Carajurin purity was previously determined by HPLC-DAD-UV as 98%, as well as by data from ESI-MS experiments and by NMR 1 H and 13 C data [ 11 ]. The compound was initially described by Chapman et al [ 13 ] and characterized by Zorn et al [ 14 ] and Devia et al [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…B. Verlot, a plant popularly known as crajiru that is native to the Amazon rainforest [ 9 ], has been used in folk medicine for wound healing, treatment of inflammation, and antioxidant activities, possibly related to the presence of anthocyanidins [ 10 ]. Analyzing different morphotypes of A. chica , we observed that its hydro-alcoholic extract is rich in anthocyanidins, mainly carajurin [ 11 ]. We recently demonstrated, through the bioguided fractionation of A. chica extract, that carajurin favored its leishmanicidal activity [ 12 ], validating our earlier identification of carajurin as a pharmacological marker for the anti-leishmanial potential of A. chica .…”
Section: Introductionmentioning
confidence: 99%
“…Factors that can explain the difference in phytochemical and biological results are probably due to the climatic differences between the two locations where the plant was collected, as well as the way of obtaining the extract ( Cortez de Sá et al, 2015 ). However, it should be noted that the difference in cytotoxicity found with our study is probably related to the exposure time used, since we used 72 h, while in the study by Cortez de Sá et al (2015) the time was reduced to 24 h. Besides, and even more important, the different morphotypes of A. chica vary in chemical composition and, consequently, in biological activity ( Moragas-Tellis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“…Publications by our research network previously reported on the leishmanicidal activity of hydroalcoholic extracts from four morphotypes of A. chica ( Moragas-Tellis et al, 2020 ). However, as the species A. chica exhibit a great set of polyphenolic compounds—mainly flavonoids—we decided to expand this study, previously done only with anthocyanidins, to evaluate whether flavones may also be involved in the leishmanicidal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation